Design and analysis of dedicated real-time clock for customized microcontroller unit - M.N. A.M. Alias; S. N. Mohyar; M. N. Isa; A. Harun; A. B. Jambek; S.A. Z. Murad (Institute of Advanced Engineering and Science, 2019)
In this paper, a Real Time Clock (RTC) system for a dedicated microcontroller is proposed to provide the customized microcontroller its own time and date system. The RTC is developed using Verilog Hardware Description Language (HDL) and simulated using Synopsys software. This RTC is developed with standard Advance Peripheral Bus (APB) to be interfacing with the microcontroller through Advanced Microcontroller Bus Architecture (AMBA). This RTC will be used as an on-chip RTC in the microcontroller system to provide precise time and date which can be used for various applications. The basic architecture of RTC, APB standard for interfacing the RTC with AMBA bus, and the result in term of RTL, waveform, and layout will be discussed in this documentation. For this research, the part covered is on the logic part of the RTC that is bus interface, register, frequency divider and counter.